The Contextual Role of Depression within Couples Experiencing Partner Violence. Issue 2 (3rd April 2018) - Brown, Cameron C.; Barros-Gomes, Patricia; Smith-Marek, Erika N.; Cafferky, Bryan; Stith, Sandra M.
ABSTRACT: Despite previous research suggesting a link between intimate partner violence (IPV) and depression within romantic relationships, few studies have examined the role of depression in couples experiencing violence. Using dyadic data of 129 heterosexual couples seeking couples therapy for high conflict including physical IPV, depressive symptoms were evaluated as a moderator in the association between psychological and physical IPV. Results indicated that moderate and high reports of women's depressive symptoms provided a context, while men's psychological abuse toward them moved from low to high, for women to be more physically abusive toward their partners. Further, low reports of women's depressive symptoms provided a context, while men's psychological abuse toward them moved from low to high, for women to be less physically abusive toward their partners. Better understanding the role of depression and how it may offer a context for physical violence assists helping professionals in holistically addressing violence within romantic relationships.